Modifikasi Perilaku Penghentian Buang Air Besar Sembarangan dengan Metode Antecedent Behavior Consequence - Jumriani Jumriani; Suriah Suriah; Muhammad Rachmat (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Some coastal communities still have the habit of defecating in open areas such as on the beach or in the garden. That is because the public does not yet know about the poor behavior related to sanitation that will affect the quality of other public health. The purpose of this study is to apply the Antecedent Behavior Consequences chain method for modification of Open Defecation behavior in child targets. This research is a quantitative study using quasy experiment design with time series design. The population is all class IV-VI at SDN Tamalate who still defecate carelessly. A sample of 37 students. The sampling technique in this study was exhaustive sampling. Data analysis using t-dependent test, Mc. Nemar and chi square with a significant level of 0.05. The results of this study indicate that there is a difference in intention score with the statistical test results of 98.18%, with a knowledge score of 10.8% to 100%, the action score from never defecated by 0.0% to 86.5% with a value p=0,000. While those who have utilized the facilities amounted to 97.3%. Suggestions for the government, should collaborate with schools and health centers to replicate or implement learning while playing with the method of snakes and ladders in providing education, about stopping open defecation in children.